2022
DOI: 10.3389/fgene.2022.901862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Normobaric Oxygen Inhalation Intervention on Microcirculatory Blood Flow and Fatigue Elimination of College Students After Exercise

Abstract: Objective: To explore the effect of normobaric oxygen inhalation intervention on microcirculatory blood flow of college students after exercise and the impact of the elimination of exercise-induced fatigue, to provide a theoretical and methodological reference for the rapid elimination of fatigue of college students after endurance exercise.Methods: Forty-eight male non-sports majors of Hubei University for nationalities were randomly divided into the control group (n = 24) and intervention group (n = 24). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The population of our study, like that of Camacho-Cardenosa [ 23 ], was composed of women and men, unlike most studies on normobaric hypoxia that have been conducted only with men [ 24 , 25 ]. We observed that, overall, the behavior of HR and SpO 2 was similar in both genders with no significant differences between them in the final initial values.…”
Section: Discussionmentioning
confidence: 99%
“…The population of our study, like that of Camacho-Cardenosa [ 23 ], was composed of women and men, unlike most studies on normobaric hypoxia that have been conducted only with men [ 24 , 25 ]. We observed that, overall, the behavior of HR and SpO 2 was similar in both genders with no significant differences between them in the final initial values.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is important to note that the hydrogen generator utilized in this study also produces oxygen. Although the concentration of oxygen inhaled into the human body is extremely minute and does not independently impact fatigue performance (The minimum concentration of oxygen required to affect fatigue and oxidative capacity is 70-96% [44,45]), there remains the possibility of a synergistic effect in combination with hydrogen.…”
Section: Accepted Manuscriptmentioning
confidence: 99%